2019
DOI: 10.1038/s41396-019-0469-x
|View full text |Cite
|
Sign up to set email alerts
|

Microbe-driven chemical ecology: past, present and future

Abstract: Recent developments in microbiome biology and chemical analytics have revealed the relevance of microbial chemical communication and its networks for microbial ecology. Deciphering chemical interactions, however, is challenging and our understanding of Microbial Chemical Ecology (MCE) under natural conditions still remains fragmented. Here, we aim to summarize what is currently known in the field of MCE. We highlight new tools and methodological challenges and discuss future perspectives of this emerging field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
73
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(82 citation statements)
references
References 79 publications
0
73
0
Order By: Relevance
“…Similarly, microbial dispersal and chemotactic behavior (Valdés-Parada et al, 2009; see e.g., Gharasoo et al, 2014;Locey et al, 2017;König et al, 2018) should be included in future. Other promising extensions are quorum sensing (Williams et al, 2007;Melke et al, 2010;Mund et al, 2016;McBride and Strickland, 2019;Schmidt et al, 2019) as regulator of biological interactions, as well as to improve the modeling of top-down control of microbial communities by predators and viruses (Pratama and van Elsas, 2018;Thakur and Geisen, 2019). Extensions along these lines will provide further insights into the biological controls on soil organic matter turnover by generating model-based hypotheses that can be tested against experimental evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, microbial dispersal and chemotactic behavior (Valdés-Parada et al, 2009; see e.g., Gharasoo et al, 2014;Locey et al, 2017;König et al, 2018) should be included in future. Other promising extensions are quorum sensing (Williams et al, 2007;Melke et al, 2010;Mund et al, 2016;McBride and Strickland, 2019;Schmidt et al, 2019) as regulator of biological interactions, as well as to improve the modeling of top-down control of microbial communities by predators and viruses (Pratama and van Elsas, 2018;Thakur and Geisen, 2019). Extensions along these lines will provide further insights into the biological controls on soil organic matter turnover by generating model-based hypotheses that can be tested against experimental evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Rhizosphere microorganisms in cropland systems are critical members of the plant microbiome regulating key aspects of plant growth, nutrient cycling, and soil health. Plant roots can promote or impede rhizosphere microorganisms' recruitment through the secretion of root exudates and volatiles (Berendsen, Pieterse, & Bakker, 2012;Broeckling, Broz, Bergelson, Manter, & Vivanco, 2008;Schmidt, Ulanova, Wick, Bode, & Garbeva, 2019). For example, recent researches have reported that rhizosphere microbial community assembly and microbial taxa colonization can be largely determined by root secondary metabolites of host plants (Veach et al, 2019), including the chemical composition and compounds quality (Gransee & Wittenmayer, 2000;Lesuffleur, Paynel, Bataille, Deunff, & Cliquet, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies include complementary analyses on host parameters of toxicological relevance such as markers of the immune system, tissue histology, developmental markers (abnormalities…). Less studies do investigate activities of microbiome members on contaminants, and bidirectional interactions ( Figure 2; Schmidt et al 2019).…”
Section: The Microbiome Responds To and Interacts With Contaminantsmentioning
confidence: 99%